Frequency of Musculoskeletal Pain Among Hospital Cleaning Workers in Tertiary Care Hospitals in Lahore. (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the frequency of musculoskeletal pain among hospital cleaning workers in tertiary care hospitals of Lahore.Methods: This cross-sectional study was conducted in University of Lahore Teaching Hospital and Services Hospital Lahore from 3rd Septemberer 2019 to 22nd February 2020. Hospital cleaning workers of either gender and all ages fulfilling the inclusion criteria were interviewed face to fac for musculoskeletal pain complaints.The data were collected using Nordic Questionnaire and analyzed through descriptive and analytical statistics.Frequency of musculoskeletal pain in workers with normal body mass index(BMI) and those with increased BMI was compared and P value was calculated with Chi-square test(P value